2017
DOI: 10.1007/s00535-017-1339-9
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease in non-clinical populations of Japan

Abstract: The presence of celiac disease in a non-clinical Japanese population was low at 0.05% and was rarely found in patients with unexplained chronic abdominal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 38 publications
1
30
0
1
Order By: Relevance
“…Despite these notions, using HLA - DQ2/DQ8 typing as a routine screening test is hindered owing to their high penetrance in general population, which limits their positive predictive values (38). Furthermore, applicability of this approach for screening CD in populations with low penetrance of these alleles is not recommended as results in high rate of undiagnosed cases (39). …”
Section: Resultsmentioning
confidence: 99%
“…Despite these notions, using HLA - DQ2/DQ8 typing as a routine screening test is hindered owing to their high penetrance in general population, which limits their positive predictive values (38). Furthermore, applicability of this approach for screening CD in populations with low penetrance of these alleles is not recommended as results in high rate of undiagnosed cases (39). …”
Section: Resultsmentioning
confidence: 99%
“…17 In a study from Malaysia, the seroprevalence of CeD was found to be 1.25% (95% CI, 0.78-1.72%) in a relatively small study including 562 young healthy volunteers. 18,19 Although there are suggestions of existence of CeD in Southeast Asia based on the reports from Japan, 19 Singapore, 20 and Vietnam, 21 the prevalence in these areas is either low or unknown. Furthermore, there are no formal reports on CeD from Taiwan, Indonesia, Korea, and many other Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in some Asian nations, CD is still considered to be either non-existent or very rare, but the incidence may be underestimated due to a lack of awareness and low suspicion of the disease [49]. In particular, official reports on CD prevalence in the paediatric Japanese population are absent, but among non-clinical adults the prevalence is about 0.05% [50]. …”
Section: Screening Strategies In Paediatric Populationsmentioning
confidence: 99%